Scorpions from Ceará State, Brazil: Distribution and ecological comments - Braga, Jacqueline Ramos Machado (2022)
Scorpions are venomous synanthropic arachnids, in 2019 they were responsible for more than 37000 cases of envenomation in the state of Ceará, Northeastern Brazil. To update the knowledge about the scorpiofauna in Ceará, a distribution list of scorpions collected/received by municipal agents of the Health Surveillance Service was performed in 165 municipalities (89%) of Ceará (2018 – 2019) and deposited in the Dr. Thomaz Corrêa Aragão Entomology Laboratory scientific collection, including species distribution maps and ecological data. This study included a total of 999 scorpions from two families (Buthidae and Bothriuridae) and eleven species. The most abundant species were: Tityus stigmurus (40.1%), Jaguajir rochae (37.2%), Bothriurus asper (8.3%) and Bothriurus rochai (6.7%), mainly inhabiting municipalities in the Caatinga biome. The first record of Tityus confluens and Tityus maranhensis in the Sobral mesoregion is herein presented, expanding the distribution of these species in Brazil.